First report on a pupping area of the tope shark Galeorhinus galeus (Carcharhiniformes, Triakidae) in the south‐west Atlantic. Issue 6 (8th November 2018) - Bovcon, Nelson D.; Cochia, Pablo D.; Navoa, Ximena; Ledesma, Pablo; Caille, Guillermo M.; Baigun, Claudio R. M.
Abstract : Neonates of the tope shark Galeorhinus galeus are captured in sport and recreational coastal fisheries from January to April each year in Engaño Bay (42° 58′–43° 41′ S), Chubut, Argentina. The presence of these neonates is the first evidence of a pupping area for this shark in the south‐west Atlantic Ocean. Knowledge of the pupping areas of chondrichthyans is important for establishing conservation measures and appropriate fishing regulations.